2015
DOI: 10.1149/2.0021510jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Dechlorination of 2-Chlorophenol on Pd/Ti, Ni/Ti and Pd-Ni Alloy/Ti Electrodes

Abstract: The 2-chlorophenol has been treated by advanced oxidation processes (AOPs) and by electrochemical oxidation, but these methods show several disadvantages, such as: high-energy costs, hazardous substances production and electrode deactivation. To avoid the problems caused by oxidation, electrochemical reduction (dechlorination) was proposed as an alternative and promising method. Pd/Ti, Ni/Ti and Pd-Ni alloy/Ti cathodes were used for electrochemical dechlorination of 2-chlorophenol. The cathodes were prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…According to Figure 6c-h, based on the photocatalytic experiments on p-nitrophenol, p-chlorophenol, and p-methylphenol, we found that the degradation efficiency of the photoelectrocatalyst for the methoxy electron-donating group was higher than that for the nitro electronwithdrawing group. This was because the electron-withdrawing groups such as nitro and chlorine groups could form conjugated and stable electrons with a benzene ring and the structure was stronger, and the hyperconjugation effect of electron donating groups caused the benzene ring to become strongly activated and easily reactive, so the characteristic group was easy to separate from the benzene ring, and the strong oxidizing group was more likely to attack the benzene ring and degrade phenols [37][38][39]. In addition, the most easily oxidized site for phenol and its derivatives was located at the ortho position to the phenolic hydroxyl group.…”
Section: Photocatalytic Degradation Of Phenolic Pollutantsmentioning
confidence: 99%
“…According to Figure 6c-h, based on the photocatalytic experiments on p-nitrophenol, p-chlorophenol, and p-methylphenol, we found that the degradation efficiency of the photoelectrocatalyst for the methoxy electron-donating group was higher than that for the nitro electronwithdrawing group. This was because the electron-withdrawing groups such as nitro and chlorine groups could form conjugated and stable electrons with a benzene ring and the structure was stronger, and the hyperconjugation effect of electron donating groups caused the benzene ring to become strongly activated and easily reactive, so the characteristic group was easy to separate from the benzene ring, and the strong oxidizing group was more likely to attack the benzene ring and degrade phenols [37][38][39]. In addition, the most easily oxidized site for phenol and its derivatives was located at the ortho position to the phenolic hydroxyl group.…”
Section: Photocatalytic Degradation Of Phenolic Pollutantsmentioning
confidence: 99%
“…4,5 It can be represented as the exchange of chemisorbed hydrogen atoms ( H ads ), which are generated on the electrode surface by the electrolysis of water or hydrogen ions with chlorine atoms. 610…”
Section: Introductionmentioning
confidence: 99%
“…The selective removal of chlorine atoms can reduce their toxicity, which makes further treatment convenient and economical. Electrocatalytic hydrodechlorination (ECH), an efficient method, has been employed in recent research due to its rapid reaction rate, mild reaction conditions, and the absence of secondary contaminants. , It can be represented as the exchange of chemisorbed hydrogen atoms ( H ads ), which are generated on the electrode surface by the electrolysis of water or hydrogen ions with chlorine atoms. …”
Section: Introductionmentioning
confidence: 99%
“…The sources of 2-monochlorophenol pollution are wastewaters from pesticide, solvent pharmaceutics, paint and paper and pulp industries as well as water disinfecting processes (Joseph et al, 2012;Muneer et al, 2012). 2-MCP is toxic, poorly biodegradable and recalcitrant and has been classified as priority pollutant by United States protection agency (USEPA) (Ajeel et al, 2015;Gonzalez et al, 2015). It imposes hazardous health effects towards humans and animals (Daraei & Kamali, 2014).…”
Section: Introductionmentioning
confidence: 99%